STUDI KEANEKARAGAMAN MAKROBENTOS DI WILAYAH KONSERVASI KURA-KURA UNIVERSITAS BENGKULU SEBAGAI SUMBER BELAJAR IPA - Winda Zulistia; Bhakti Karyadi; Agus Susanta (University of Bengkulu, 2017)
This study aims to determine the diversity of macrobentos that exist in the turtle conservation pond University of Bengkulu which serve as a source of learning science class VII MTsN 2 Bengkulu City. This research was conducted in February 2017 until May 2017. The sampling of macrobentos using a quadrant transect measuring 1x1 meter made of 6 quadrants. Based on the results of research conducted obtained 1,086 individuals belonging to macrobentos belonging to 3 genus namely, Bellamnya, Faunus, and Pomaceae. The data obtained were calculated based on macrobentos community structure consisting of population density (KP), relative abundance (KR), presence frequency (FK), Diversity Index (H ') and dominance index (C). The macrobentos diversity index found in turtle conservation ponds is below 1.5, with the result it can be said that in both turtle conservation ponds it has low macrobentos diversity. Development of learning refers to the modified Dick & Carey model. The lessons developed include Syllabus, RPP, LKPD, and performance appraisal instruments that are viewed from the students' process skills. The result of the validation of learning development shows that the teaching materials developed are very feasible in the test try to learners. The results showed that the average of students' process skills from the aspect of the highest performance performance was in good criteria. This is indicated by the percentage that reaches 67%. While the criteria include very good reached 33%. While for the result of measurement of process skill of student which counted by classical which counted on each indicator included into good category and very good.